2018
DOI: 10.2196/mhealth.9999
|View full text |Cite
|
Sign up to set email alerts
|

How New and Expecting Fathers Engage With an App-Based Online Forum: Qualitative Analysis

Abstract: BackgroundBreastfeeding is important for infants, and fathers are influential in supporting their partner in their decision to breastfeed and how long they breastfeed for. Fathers can feel excluded from traditional antenatal education and support opportunities but highly value social support from peers. Online health forums can be a useful source of social support, yet little is known about how fathers would use a conversation forum embedded in a breastfeeding-focused app. Milk Man is a mobile app that aimed t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(77 citation statements)
references
References 28 publications
2
40
0
Order By: Relevance
“…Almost all the most read library articles and external links followed from the app originated from links within the conversation forum. Our team has previously reported how fathers have used the app to seek and offer social support [31]. This finding is consistent with that of other researchers who have reported that fathers use parenting forums to find emotional support [28], with parenting websites being particularly helpful in supporting men’s transition to fathering [49].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Almost all the most read library articles and external links followed from the app originated from links within the conversation forum. Our team has previously reported how fathers have used the app to seek and offer social support [31]. This finding is consistent with that of other researchers who have reported that fathers use parenting forums to find emotional support [28], with parenting websites being particularly helpful in supporting men’s transition to fathering [49].…”
Section: Discussionsupporting
confidence: 87%
“…Users could swipe the notification to be taken directly to the new content in the conversation. The conversation forum was monitored by researchers throughout the study [31]. The app’s engagement strategy was underpinned by gamification.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Messages and library resources for the intervention and control groups will be developed separately and delivered to participants through a smartphone app. The design, development and evaluation of the app will be adapted from previous studies on mHealth and infant feeding [ 91 , 96 , 99 , 113 , 114 , 115 , 116 , 117 ].…”
Section: Methodsmentioning
confidence: 99%
“…A quasi-experimental study on the “Growing Healthy mHealth Program” found no differences in exclusive breastfeeding rates between the intervention and control groups [ 96 ]. Other studies have focused on promoting exclusive breastfeeding through fathers [ 97 , 98 , 99 ]. Mobile applications have also been developed in other countries such as Thailand [ 92 ] and the United States [ 100 , 101 , 102 ], which have focused on the feasibility and acceptability of the mobile application, though more studies on their effectiveness are needed [ 103 , 104 ].…”
Section: Introductionmentioning
confidence: 99%